Comprehensive Green Development and Circular Business Economy Practices Harmonized with Future SDG Realization at Management Accounting Perspective - Huy, Pham Quang; Phuc, Vu Kien (Journal of Environmental Accounting and Management, 2026)
This study aims at exploring the relationship between digitalized management accounting system (DMAS) and Sustainable Development Goals (SDGs). It also investigates the function of performance management of circular economy practices integrated with inclusive green growth (CEIGG) in the relationship between DMAS and SDGs. Furthermore, it seeks to enhance understanding of how government policy (GP) influences the direct relationships between DMAS and CEIGG, DMAS and SDGs as well as the indirect relationship between DMAS and SDGs via CEIGG, utilizing a moderated mediation model and a hybrid analytical approach with SEM and fuzzy-set qualitative comparative analysis together with a sample of public sector accountants. It revealed that DMAS exerted a considerable and positive impact on SDGs. Additionally, it indicated that CEIGG partially mediated the link between DMAS and SDGs. Furthermore, the results indicated that GP significantly moderated the direct relationships between DMAS and CEIGG, DMAS and SDGs as well as the indirect interaction between DMAS and SDGs via CEIGG. The fsQCA results underscored complex causal relationships among the pertinent factors. Policymakers and practitioners could leverage this study to enhance comprehension of DMAS potential operations and to elucidate strategies, processes, management for the execution as well as optimization of public sector circular economy (CE) practices integrated with inclusive green growth (IGG).